DELINEATION POROSITY OF CARBONATE ROCK FROM PETROPHYSICS USING SIMULTANEOUS SEISMIC INVERSION AND MULTI-ATTRIBUTE ON âJULIâ FIELD, EAST JAVA BASIN - Julianti, Dwi
Indonesia have much potential in energy resources. The exploration and exploitation activities in Indonesia help to fulfill the energy needs in Indonesia. The exploration activities in Indonesia help to find the potential energy resources such oil and gas. Reservoir characterization with petrophysics can be applied to define the litology, porosity, water saturation, and permeability the rock under the ground. One of the important aspects to define the reservoir is to understand the porosity of the target reservoir. In this research, will calculated the neutron-density porosity in the reservoir using petrophysics analysis. From the sensitivity analysis Simpedance can be used to devided the shale and carbonate area. After defining the porosity of the reservoir, in this thesis will be applied the seismic inversion to get volume of P-impedance, S-Impedance, and density for identifying the target area. The porosity generated before will be mapped by applying multi-attribute. The combination of the low density area and high porosity area on both maps can be used to see the target area to convince where the next area for well production.